Sealing ability of hydroxyapatite as a root canal sealer: in vitro study - , Widowati Witjaksono ([Yogyakarta] : Airlangga University Press, 2007)
Hydroxyapatite (HA) is the most thermodynamically synthetic calcium phosphate cement, and has indicated useful as a sealer because can seal a furcation perforation, is shown to be biocompatible and also has potential to promote the healing of bone in endodontic therapy. The objective of this study is to determine the sealing ability of HA produced by School of Engineering, University Sains Malaysia (USM) when used as a sealer in root canal obturation, compare with Tubli-seal (Zinc-Oxide base) and Sealapax (Calcium Hydroxyde base) sealers. Forty five single rooted human anterior teeth were instrumented and randomly divided into three experimental Groups&nbsp